Violência contra o idoso no estado de Minas Gerais: análise das notificações em 2009-2012. - Rezende, Mariana Marquez de (2013)
Over the past forty years, the elderly population was the fastest growing in Brazil. Due to its characteristics of greater physiological vulnerability and fragility, the elderly becomes potential victim to the growing violence of everyday life. The increasing search for data on violence against elderly appear as promising action aimed at transforming public policy issue and openness for dialogue between government and society spheres aimed alleviate this situation. For proper planning assistance to the population 's access to critical health information, as in the case of this study, access to database information system Interlocutory Notice (SINAN). The objectives of this study were to describe the epidemiology of reported cases of violence against the elderly in the State of Minas Gerais; dDescrever incidence, mortality and case fatality reported by type of violence and sex; verify the association between types of violence and sex; analyze the completeness of the notification fields filled record of violence against the elderly; verify which municipalities of Minas Gerais who perform the reporting of cases of violence and map them. This ecological study. Calculation of incidence rates, mortality and lethality; calculation of sex ratio and georeferencing in data analysis descriptive statistics were used. 2,042 cases reporting of violence against elderly in the years 2009 and 2012 were analyzed. We observed predominant color white or mulatto The area of highest incidence was the urban site and the actual residence of the victim. The women were the main victims and the type of physical violence was prevalent, as the use of physical force. The characterization of the author of the act was greater for males. The occurrence of deaths was small, being 1.6 % in 2012 and none in 2009. The majority of cases received high (> 70 %). Regarding notifying municipalities, were few in 2009, an increase in 2012, but with decreased quality of information. It is concluded that most cases of violence against the elderly occurred in females, practiced by most of the male resident sex in the urban area, with the occurrence of the act in the victim's own residence. The highest incidence was the case with physical violence by use of physical force.